Institutional territories, communal territories. Approaches to multi-territoriality in Nazareno (Salta-Argentina) (Huellas, 2021)
The Nazareno communities, located in the northwest of the Salta province, present a multiterritorial reality in their spatial configuration, manifested by the definitions given by state institutions and those configured by the inhabitants themselves. The objective of this work is to expose the different existing graphic elements of the communities and to contrast them with the “reality of the field” in order to understand the tensions that originate in the superposition of the territorial definition of the same place.The article is based on two types of approaches, on the one hand the archival work and bibliographic search of the area and the subject and on the other, the field work with an ethnographic approach, which brings us closer to the perspectives of the inhabitants of the place. This work has made it possible to demonstrate that there is no univocal territory, as shown in the figures, and indeed that there is a multi-territorial identity. From this point we propose the understanding of the daily existence of geographical differences.
Keywords: Geographical Dissidence; Ethnographic Work; Multiterritoriality